2017
DOI: 10.1038/onc.2017.387
|View full text |Cite|
|
Sign up to set email alerts
|

IL6 derived from cancer-associated fibroblasts promotes chemoresistance via CXCR7 in esophageal squamous cell carcinoma

Abstract: Various factors and cellular components in the tumor microenvironment are key drivers associated with drug resistance in many cancers. Here, we analyzed the factors and molecular mechanisms involved in chemoresistance in patients with esophageal squamous cell carcinoma (ESCC). We found that interleukin 6 (IL6) derived mainly from cancer-associated fibroblasts played the most important role in chemoresistance by upregulating C-X-C motif chemokine receptor 7 (CXCR7) expression through signal transducer and activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 46 publications
1
109
2
Order By: Relevance
“…The prognosis for ESCC remains poor largely due to late diagnosis and propensity for metastasis. Despite significant advances in diagnostic techniques and therapeutic approaches, the overall 5-year survival rate ranges from 15 to 25% (3)(4)(5). Recent studies have shown that many malignancies contain a cell subpopulation known as cancer stem cells (CSCs), which are thought to cause aggressive tumor behavior and therapy resistance and have high tumor-initiating capacity, thereby leading to recurrence, metastasis, and insufficient response to conventional therapies (6).…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis for ESCC remains poor largely due to late diagnosis and propensity for metastasis. Despite significant advances in diagnostic techniques and therapeutic approaches, the overall 5-year survival rate ranges from 15 to 25% (3)(4)(5). Recent studies have shown that many malignancies contain a cell subpopulation known as cancer stem cells (CSCs), which are thought to cause aggressive tumor behavior and therapy resistance and have high tumor-initiating capacity, thereby leading to recurrence, metastasis, and insufficient response to conventional therapies (6).…”
Section: Introductionmentioning
confidence: 99%
“…Here we characterized precisely the mechanisms by which CA-MSCs exert their biological functions, in particular the role played by the cytokines produced by these cells (CXCR1/2 ligands). We studied the role played by these ligands, while several other authors have mainly focused their attentions on IL-6 and its role in cancer cell proliferation [17,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…CAFs already contribute to chemoresistance by themselves via various mechanisms: PAI-1, a cytokine produced by CAFs, activates Erk/Akt signaling and suppresses caspase-3 activation, which is necessary for tumor apoptosis following chemotherapeutic stress (Che et al, 2018). Similarly, interleukin 6 (IL6) is also produced predominantly by CAFs and induces expression of resistance-mediating CXCR7 in tumor cells (Qiao et al, 2018;Xu et al, 2018). Especially under hypoxic conditions, CAFs produce high levels of TGFβ, which induces stem celllike properties in tumor cells including increased resistance to chemotherapy (Tang et al, 2018).…”
Section: Carcinoma-associated Fibroblastsmentioning
confidence: 99%